Analisis Yuridis Terhadap Kewajiban Magang dan Relevansi Dengan Pengangkatan Pejabat Pembuat Akta Tanah (Ppat) - Eka Cristy Sembiring (Universitas Harapan Medan, 2021)
The Official for this research is to discover the obligation of candidates of PPAT (Officials Empowered to Draw up Land Deeds), to take an internship: in which they are obliged to understand and help the process of land activity and service, recruitment and verification process of registered deeds as well as verification of juridical data op application for land title. The primary task of PPAT is carry out part land registration activities by drawing up deeds as evidence for having taken particular legal actions regarding land title or ownership right over apartment units, that is made the ground for registration of changes in land registration resulted from the legal actions. This research employs normative juridical method in form of document study, which studies the obligations of candidates of PPAT (Officials Empowered to Draw up Land Deeds) to take an internship and its relevance with appointment of PPAT. This research is descriptive; it describes the obligation of PPAT to take an internship. The legal materials used in this research are sourced from results of library research such as primary, secondary and tertiary legal materials. In addition, this research is supported by interviews with relevant parties to complete this thesis. These legal materials that have been collected are firstly described by legal and non-legal proportion, then interpreted to be further estimated and evaluated.